School reform proposals : the research evidence - Molnar, Alex (Research in educational productivity., 2002)
An examination of the research relating to school reform proposals. It features essays covering: early childhood education; class-size reduction in grades K-3; small schools; grouping students for instruction; public schools and their communities; teacher characteristics; and more.